A Case Report of Wellens’ Syndrome: An Ominous Sign of Left Anterior Descending Artery Critical Stenosis and Impending Anterior Myocardial Infarction - Willim, Herick Alvenus; Agustyana, Andini; Arilaksono, Dwisetyo Gusti; Proklamartina, Nurnajmia Curie; Furqon, Muhammad (Indonesian Journal of Medicine, 2020)
Background: Wellens’ syndrome is a potentially life-threatening condition, characterized by biphasic or deeply inverted T-waves changes in electrocardiographic (ECG) precordial leads, which associated with critical stenosis of left anterior descending (LAD) coronary artery and impending anterior myocardial infarction in patients presenting with unstable angina. This syndrome is an important sign for clinicians because delay in coronary angiography and revascularization may lead toanterior myocardial infarction, left ventricular dysfunction, and even death.Case presentation: A 50-year-old woman came to emergency department in a hospital in Bontang, with new onset intermittent typical chest pain lasting since 3 days. She had history of hypertension without regular medication. Physical examination was in normal ranges. An ECG obtained during chest pain-free period showed Wellens’ type A with biphasic T waves in V2-V6 and preserved R-wave progression. Troponin T was slightly elevated. During observation, the ECG pattern changed from Wellens’ type A to Wellens’ type B with deep T-wave inversions in V2-V6 and preserved R-wave progression.Results: The patient was initially treated with conservative treatment. On the next day, she was referred to percutaneous coronary intervention-capable hospital in Samarinda. Coronary angiography revealed 90% stenosis of mid LAD. A drug-eluting stent was successfully implanted with restoration of LAD flow. She was discharged on the following day in good condition with medication of dual antiplatelet therapy, angiotensin-converting enzyme inhibitor, beta-blocker, and statin.Conclusion: Clinicians should be aware of the ECG changes in Wellens’ syndrome, which may occur during pain-free period. Early recognition is crucial to avoid the development of anterior myocardial infarction. Immediate coronary angiography and revascularization is needed.Keywords: Wellens’ syndrome, critical stenosis, myocardial infarctionCorrespondence: Herick Alvenus Willim. Dr. Agoesdjam General Public Hospital, Ketapang, West Kalimantan. Email: herick_alvenus@yahoo.co.id.Indonesian Journal of Medicine (2020), 05(03): 246-252https://doi.org/10.26911/theijmed.2020.05.03.10